Vínculos afetivos na educação infantil: desafios na auto(trans)formação permanente de professores - Pigatto, Carolina Zasso (2016)
This dissertation is included in the line of research entitled Formation, Knowledge and Professional Development of the Graduate Program in Education at the Federal University of Santa Maria/RS. The justification for this research relies on the author s memories and experiences. For the development of this study, a discussion with teachers of a municipal school in Santa Maria/RS was carried out. The objective of the research was to understand how the teachers of a municipal children s school in Santa Maria/RS see the affectional bonds in children s education and in their own permanent self(trans)formation. The methodology used was based on a qualitative approach of the case study type; semi-structured interviews were carried out in order to collect data; then, the generating themes came up to stimulate the Investigative-formative Dialogic Circles in a virtual way, inspired by the Freirean Culture Circles, as developed by Kaufman (2015), having been analyzed as virtual interviews because they had not been actually carried out. The data have been interpreted using a hermeneutic analysis, which made it possible to interpret the different expressions of the participant teachers (speech, silence, gestures) and their understanding. The theoretical framework on affectivity and affectional bonds included authors like Wallon (1975, 1971), Vygotsky (2003), Paulo Freire (2006) and Pichon-Riviere (2007). To justify and deepen the theme of self (trans) formation, the presuppositions of Imbernón (2010), Freire (1987,1997, 2000, 2006, 2009, 2014), among others have been used. The research pointed out that the teachers emphasize the importance of group work not only for the educational work itself but also for the development of the children; they also mentioned that the affectional bonds are directly related and thus reflect in their own work. In this sense, they indicated that the socialization moments broadened knowledge and self(trans)formations which were considered relevant to their activity. The professionals also mentioned the importance of continuing education.